La désaisonnalisation pour le non-spécialiste - Cholette, Pierre (L'Actualité économique, 1983)
AbstractThis paper provides simple descriptions and interpretations of the components found in time series: the trend, the cycle, the seasonal, the trading-day and the irregular components. Furthermore, the necessity and the justification ofseasonal adjustment are explained. It is however reminded the seasonally adjusted series should not be used for model building.